2011
DOI: 10.1177/875687051103000404
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Large Lecture, Fully Online, and Hybrid Sections of Introduction to Special Education

Abstract: This study evaluated the effectiveness of flexible learning options at a university serving multiple geographic areas (including remote and rural areas) and age groups by teaching an introduction to special education course to three large groups of pre-teacher education majors using three modes of instruction. The university offered sections as (a) a traditional large lecture class, (b) a fully online asynchronous course, and (c) a hybrid course with lecture and asynchronous online instruction. Data analysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Online education has been found to promote accessibility to educational opportunities for non-traditional students and those who live in remote regions (Chau, 2010;Robina & Anderson, 2010). Also, students often report valuing the flexibility of online courses so they can pursue their academic career while holding jobs and maintaining personal obligations (Chau, 2010;O'Brien, Hartshorne, Beattie, & Jordan, 2012;Vernon-Dotson, Floyd, Dukes, & Darling, 2014). Studies have found that some online learning models are student-centered (Gilboy, Heinrichs, & Pazzaglia, 2015), increase student engagement (Anderson, 2008;Herrington & Herrington, 2006), and assist in the development of students' technological skills which can be applied in their workplace (Chau, 2010).…”
Section: Descriptions Of Distance Learning Delivery Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online education has been found to promote accessibility to educational opportunities for non-traditional students and those who live in remote regions (Chau, 2010;Robina & Anderson, 2010). Also, students often report valuing the flexibility of online courses so they can pursue their academic career while holding jobs and maintaining personal obligations (Chau, 2010;O'Brien, Hartshorne, Beattie, & Jordan, 2012;Vernon-Dotson, Floyd, Dukes, & Darling, 2014). Studies have found that some online learning models are student-centered (Gilboy, Heinrichs, & Pazzaglia, 2015), increase student engagement (Anderson, 2008;Herrington & Herrington, 2006), and assist in the development of students' technological skills which can be applied in their workplace (Chau, 2010).…”
Section: Descriptions Of Distance Learning Delivery Optionsmentioning
confidence: 99%
“…As commonly noted, distance education is a convenient option for non-traditional students because it allows them to pursue their education with flexibility, which is critical if they are balancing coursework and a complex schedule. One study noted that traditional undergraduate students felt that online course work was difficult and time-consuming, while non-traditional students indicated that they felt more comfortable in that educational setting (O'Brien et al, 2012). Understanding the demographic trends of students who opt-in for specific delivery models would enable educators to better meet students' needs.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…A third type of learning environment combines the features of both traditional face-to-face instruction with online learning techniques [23,24,25]. This is referred to as "blended" or "hybrid courses."…”
Section: Blended Learning Environmentmentioning
confidence: 99%
“…Since hybrid or blended modes seek to maximize the best elements of online and face-to-face learning (O'Brien, Hartshorne, Beattie, & Jordan, 2011), considerable research has been conducted to compare online and blended learning. Overbaugh and Nikel (2011) conclude in one such study that students in both delivery modes were satisfied with the course and had equally high degrees of perceived learning.…”
Section: Figure 1 Delivery Mode Continuum and Interaction Typementioning
confidence: 99%